Student profile of a brazilian public dental school - Tango, Rubens Nisie [UNESP]; Komori, Paula Carolina [UNESP]; Araújo, Luiz Fernando; Bardini, Vivian Silveira Dos Santos [UNESP]; Kaminagakura, Estela [UNESP] (Editora Cubo, 2021)
Objetive: The aim of this study was to assess the profile of dental students at the ICT/CSJCUNESP School of Dentistry and their preferred studying style. Material and methods: Data on age, sex, place of residence, first-choice course, secondary education background and study method preference were collected from an online questionnaire given in the second year dental materials course (first class) of the day and evening courses of the years 2016 to 2019. All data were tabulated and submitted to one-way ANOVA and to t test, both with a= 0.05. Pearson correlation test was performed between demographic data and study method preference (α = 0.05). Results: Most of the students were women living in São José dos Campos city who had chosen Dentistry as their first-choice course. Many were originally from other cities and lived in shared accommodation with friends. The majority stated that private high school was their main educational background. The students’ age and place of living showed to correlate with study method preference. Conclusion: Although ICT/CSJCUNESP students were from millennial and postmillennial generations, students with public secondary education preferred studying alone, while those from private education preferred studying in group.
O perfil do aluno de uma faculdade de odontologia pública brasileira
Keywords: Dental health education; Dental students; Formative feedback; Higher education